STUDIES ON SURVIVAL AND DISPERSAL OF PIGEONPEA PHYTOPHTHORA - Y. L. NENE, V. S. BISHT* AND (Indian Phytopathology, 2002)
Leaf-baiting and a new selective medium were used to determine that Phytophthora drechsleri f.sp. cajani (Pdc) survives for at least one year in infected plant debris in the field. There was no evidence of seed transmission. Splashing rain and wind contributed to short distance dispersal of Pdc while water flowing from a Pb-infested field carried inoculum to other fields.